Analysis of Financial Accounting Problems of Human Resources - Wang, Lizhen (Journal of Theory and Practice of Management Science, 2023)
Since the reform and opening-up in the past 40 years, our comprehensive strength has been continuously improving, the level of economic development is also becoming higher, all fields have a more obvious development, at the same time also has a greater space for development. With it came many new things and new industries, which are the expression of social progress. With the progress and development of The Times, the modernization of enterprises is developing faster and faster, the scale is obvious, and the investment of enterprises in human resources is gradually increasing. Because of this, the position of human resources financial accounting is more and more important, so we should conduct in-depth research on it. This paper analyzes and explores these problems from four angles.